2008
DOI: 10.1111/j.1532-5415.2007.01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Drug Use and Risk of Pneumonia in Elderly People

Abstract: Use of antipsychotics in elderly people is associated with greater risk of pneumonia. This risk is highest shortly after the initiation of treatment, with the greatest increase in risk found for atypical antipsychotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
154
2
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(178 citation statements)
references
References 34 publications
8
154
2
8
Order By: Relevance
“…The higher rate of chest infections after prescription of atypical antipsychotics is in line with Knol et al's study, 7 where a stronger association between atypical antipsychotics and pneumonia was also seen, as compared with conventional antipsychotics. Users of conventional antipsychotics had a higher risk of death from infections, including pneumonia, than users of atypical antipsychotics in Setoguchi et al's study, 4 but the difference was not statistically significant.…”
Section: Comparison With Existing Literaturesupporting
confidence: 79%
See 1 more Smart Citation
“…The higher rate of chest infections after prescription of atypical antipsychotics is in line with Knol et al's study, 7 where a stronger association between atypical antipsychotics and pneumonia was also seen, as compared with conventional antipsychotics. Users of conventional antipsychotics had a higher risk of death from infections, including pneumonia, than users of atypical antipsychotics in Setoguchi et al's study, 4 but the difference was not statistically significant.…”
Section: Comparison With Existing Literaturesupporting
confidence: 79%
“…6 Older patients currently using antipsychotic medicines, when compared with those not currently using them, were noted to be at higher risk for pneumonia with an adjusted odds ratio of 1.6 (95% confidence interval [CI] = 1.3 to 2.1) in a nested case control study on pharmacy dispensing and hospital discharge registrations. 7 Users of atypical antipsychotics showed a higher risk for pneumonia than users of conventional antipsychotics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, frail elderly persons may experience delirium as a prodromal symptom of pneumonia and, as a consequence, receive antipsychotic treatment. This increases the risk of protopathic bias in observational studies, that is, wrong attribution of the onset of pneumonia to antipsychotic administration [4]. Nevertheless, Trifirò et al [5] and Huybrechts et al [7] observed that the risk of pneumonia appears to be dose-dependent, strengthening the hypothesis that antipsychotics are involved in the causal pathway.…”
mentioning
confidence: 93%
“…Three studies demonstrated that the risk of pneumonia varies by antipsychotic class, with a higher risk being attributed to atypical antipsychotics [4,[6][7][8][9]. A more recent finding is the demonstration of a differential risk associated with individual antipsychotic drugs [5,7].…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation